Analisis Framing Model Zhongdan Pan dan Gerald M.Kosicki dalam Pemberitaan Pelantikan Panglima Tni Yudo Margono Media Detik.Com dan CNNindonesia.com Edisi Desember - Dewi Nurkomalasari; Hendra Setiawan (Departement of Mathematics Education, 2023)
The purpose of this study is to find out a framing analysis (frame or delivery of news), which uses two mass media including detik.com and cnnindonesia. To find out the comparison of the two-mass media, the researcher used framing analysis according to the theory of Zhongdan Pan and Gerald M. Kosicki. In this theory there are 4 structures, namely syntax, script, thematic, rhetorical. In addition, this study also uses a qualitative descriptive method, which collects data in terms of observing and noting. The news on 19 December 2022 discussed the inauguration of the TNI Commander, Admiral Yudo Margono, who was appointed by President Joko Widodo, so that General Andika Perkasa was honorably discharged.